2022
DOI: 10.3390/ma15238641
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PLA/PCL/Green Mussel Shells Hydroxyapatite (HA) Biocomposites Prepared by Chemical Blending Methods

Abstract: Recently, there has been an increase in the number of studies conducted on the process of developing hydroxyapatite (HA) to use in biocomposites. HA can be derived from natural sources such as bovine bone. The HA usage obtained from green mussel shells in biocomposites in this study will be explored. The research goal is to investigate the composition effect of biomaterials derived from polycaprolactone (PCL), polylactic acid (PLA), as well as HA obtained from green mussel shells with a chemical blending metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…The XRD diffractogram showed that the peaks of PCL decreased and widened as the BT concentration increased, whereas the peaks of BT increased, especially at 2ϴ = 50.9 for samples coated with (2:1 BT:PCL). This study’s results agree with those of a study by Moura et al 66 and Ismail et al 67 that contrasted different concentrations of hydroxyapatite combined with polymer material. As the concentration of ceramic increased, the XRD diffractogram revealed that the peaks of polymer reduced while the peaks of ceramic increased.…”
Section: Resultssupporting
confidence: 92%
“…The XRD diffractogram showed that the peaks of PCL decreased and widened as the BT concentration increased, whereas the peaks of BT increased, especially at 2ϴ = 50.9 for samples coated with (2:1 BT:PCL). This study’s results agree with those of a study by Moura et al 66 and Ismail et al 67 that contrasted different concentrations of hydroxyapatite combined with polymer material. As the concentration of ceramic increased, the XRD diffractogram revealed that the peaks of polymer reduced while the peaks of ceramic increased.…”
Section: Resultssupporting
confidence: 92%
“…Materials used in this investigation included HA made from waste green mussel shells and stainless steel AISI 316L [23]. The HA powder was baked in an oven at 120°C for 20 minutes to remove moisture before being used for thermal coating.…”
Section: Materials and Coating Preparationmentioning
confidence: 99%
“…Combining PLA with different materials can potentially improve its properties. Ismail et al [16] developed biocomposite from PLA, polycaprolactone (PCL), and hydroxyapatite derived from green mussel shells.…”
Section: Introductionmentioning
confidence: 99%